Skyrmion States in Disk Geometry - Winkler, Thomas Brian; Litzius, Kai; De Lucia, Andrea; Weissenhofer, Markus; Fangohr, Hans; Klaeui, Mathias (Physical Review Applied, 2021)
In this work, we explore the stability of magnetic skyrmions confined in a disk geometry by analyzing how to switch a skyrmionic state in a circular disk into a uniformly magnetized state when applying an external magnetic field. The technologically highly relevant energy barrier between the skyrmion state and the uniformly magnetized state is a key parameter needed for lifetime calculations. In an infinite sample, this relates to the out-of-plane rupture field against the skyrmion-core direction, while in confined geometries the topological charge can also be changed by interactions with the sample edges. We find that annihilating a skyrmion with an applied field in the direction of the core magnetization - we call this expulsion - the energy barrier to the uniform state is generally around one order of magnitude lower than the annihilation via the rupture of the core in the disk center, which is observed when the applied field is acting in the direction opposite to the core magnetization. For the latter case a Bloch point (BP) needs to be nucleated to change the topological charge to zero. We find that the former case can be realistically calculated using micromagnetic simulations but that the annihilation via rupture, involving a Bloch point, needs to be calculated with the Heisenberg model because the high magnetization gradients present during the annihilation process cannot be accurately described within the micromagnetic framework.
CRIS-Team Scopus Importer:2023-03-27